2015
DOI: 10.1177/0829573515594372
|View full text |Cite
|
Sign up to set email alerts
|

When Ideals Get in the Way of Self-Care

Abstract: In the current study, we investigated whether adolescents high in perfectionism are prone to experiencing self-stigma for seeking psychological help. This work is based on the premise that the need to seek help for psychological difficulties is not consistent with idealistic personal goals of perfectionistic young people and their desire to retain an idealistic self-image. A sample of 85 high school students completed the Child and Adolescent Perfectionism Scale, the Self-Stigma of Seeking Help Scale, and a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 49 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…Higher self-stigma for needing help was also correlated with greater self-oriented perfectionism among high school students (Zeifman et al, 2015).…”
Section: Key Practitioner Messagementioning
confidence: 89%
“…Higher self-stigma for needing help was also correlated with greater self-oriented perfectionism among high school students (Zeifman et al, 2015).…”
Section: Key Practitioner Messagementioning
confidence: 89%
“…In recent years, college students (and especially those who identify as women or genderqueer) have been reporting increasingly high levels of mental health problems, and stigma is a well-known factor in college students’ decisions not to seek mental health treatment (Chen et al, 2016; Smith & Applegate, 2018). Given that low self-compassion and unfavorable attitudes about mental disorders and their treatment are linked with the various forms of maladaptive perfectionism (socially prescribed perfectionism, perfectionistic self-presentation, and effortlessly perfect self-presentation; Abdollahi et al, 2017; Berenson et al, 2018; Shannon et al, 2018; Zeifman et al, 2015) that have become increasingly characteristic of young adults in the United States (Curran & Hill, 2019), interventions to bolster indifference to stigma via increased self-compassion may be especially useful in this at-risk population. Longitudinal studies should also test whether interventions designed to increase self-compassion over longer periods of time (e.g., see Neff & Germer, 2013) might lead to lasting reductions in self-stigma about mental disorders and treatment, and increases in treatment utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Wilson et al (2007) found that those with greater internalizing symptoms were more likely to say they would seek help from no one, while Rickwood et al (2005) found that males with internalizing symptoms were less likely than females with internalizing symptoms to seek treatment. Zeifman et al (2015) identified stigma as a barrier to help-seeking in adolescents with internalizing symptoms but found that this effect was moderated by levels of MHL.…”
Section: Study Purposementioning
confidence: 99%
“…The present study contributes to existing research on mental health help-seeking in adolescence in several ways. First, there has been little investigation into help-seeking for internalizing symptoms within a high school setting (Wilson, Rickwood, & Dean, 2007;Zeifman, Atkey, Young, Flett, Hewitt, & Goldberg, 2015). Wilson et al (2007) found that those with greater internalizing symptoms were more likely to say they would seek help from no one, while Rickwood et al (2005) found that males with internalizing symptoms were less likely than females with internalizing symptoms to seek treatment.…”
Section: Study Purposementioning
confidence: 99%